(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine pattern of anaerobic microbial infection in patients with diabetic foot ulcers and the effect of those infections on surgical outcomes following management. Study Design: Analytical (Descriptive) Study. Setting: Department of Medicine, Hayatabad Medical Complex, Peshawar, Khyber Pakhtunkhwa. Subjects and Methods: This study was conducted from 1st July 2023 to 31st December 2024 at the Department of Medicine, Hayatabad Medical Complex, Peshawar, Khyber Pakhtunkhwa. A total of 125 patients of both genders with DM Type II diabetic foot ulcers were included in the study. The following parameters were considered: age, gender, education, MR number, contact number, locality, duration of T2DM, outcomes, complications and culture reports from swabs. The data was added to Microsoft Excell and transferred to SPSS version 23.0 for data analysis. The Pearson chi-square test was utilized to measure the correlation. Results are shown in the form of description, tables and charts. Results: The study recorded 100% infection rate among the diabetic foot ulcer subjects Age range in this study was from 20 to 80 years with mean age of 57.752±6.89 years. Pepto streptococcus was found in 22.4% patients, Bacteroides fragilis in 12%, Clostridium perfringens in 15.2% and E. coli was seen in 16%. In terms of outcomes following management, healing was seen in 80.8% patients, toe Amputation in 13.6% and limb amputation in 5.6%. Conclusion: Pepto streptococcus and Bacteroides were the most common microorganisms found in culture swabs from diabetic foot ulcers and most patients from these microbes ultimately had to undergo amputation.